Therapeutic strategies to target RAS-mutant cancers. Issue 11 (November 2018) - Ryan, Meagan; Corcoran, Ryan
Abstract RAS genes are the most commonly mutated oncogenes in cancer, but effective therapeutic strategies to targetRAS -mutant cancers have proved elusive. A key aspect of this challenge is the fact that direct inhibition of RAS proteins has proved difficult, leading researchers to test numerous alternative strategies aimed at exploiting RAS-related vulnerabilities or targeting RAS effectors. In the past few years, we have witnessed renewed efforts to target RAS directly, with several promising strategies being tested in clinical trials at different stages of completion. Important advances have also been made in approaches designed to indirectly target RAS by improving inhibition of RAS effectors, exploiting synthetic lethal interactions or metabolic dependencies, using therapeutic combination strategies or harnessing the immune system. In this Review, we describe historical and ongoing efforts to targetRAS -mutant cancers and outline the current therapeutic landscape in the collective quest to overcome the effects of this crucial oncogene. Effective therapeutic strategies to target RAS-mutant cancers have proved elusive, but in the past few years, several promising strategies have been tested in clinical trials. The authors describe historical and ongoing therapeutic approaches based on the direct or indirect targeting of RAS. Key points RAS is the most commonly mutated oncogene in cancer. Direct inhibition of oncogenic RAS has proved difficult, hindering the development of effective therapies forRAS -mutant cancers. Renewed efforts to target mutant RAS directly have yielded promising efficacy outcomes in preclinical studies. Targeting key effector pathways or vulnerabilities inRAS -mutant cancers offers a promising alternative therapeutic approach.